Hell or high water : James White's disputed passage through Grand Canyon, 1867 - Adams, Eilean, 1923- (Utah State University Press, 2001)
Although John Wesley Powell and party are usually given credit for the first river descent through the Grand Canyon, the ghost of James White has haunted those claims. White was a Colorado prospector, who, almost two years before Powell's journey, washed up on a makeshift raft at Callville, Nevada.